Bioinspired cross-linking of preceramic polymers via metal ion coordination bonding. Issue 13 (October 2021) - Martin, Kara L.; Parvulescu, Maria J.S.; Patel, Tulsi A.; Mogilevsky, Pavel; Key, Thomas S.; Thompson, Christina M.; Dickerson, Matthew B.
Graphical abstract: Highlights: Metal ion coordinating preceramic polymers were inspired by biological systems and synthesized via post polymerization polymer modification. Metal ion concentration influences degree of preceramic polymer crosslinking, effecting rheology and ceramic yield. Zinc ions serve as a transient processing aid, allowing for conversion of polysiloxane to ceramic, yet Zn does not appear in the final product due to its evaporation at high temperature. Ceramic nanocomposites of SiC with TiC or Y-based compounds formed through the conversion of polymers cross-linked with Ti 4+ or Y 3+ . Highly modular and tailorable polymers allow for the production of a variety of ceramic compositions through the simple substitution and chelation of inexpensive metal ions. Abstract: Metal coordination chemistry is common in biology, with many proteins containing metal ion-based structural motifs or catalytic centers. An interesting example of nature's use of coordinate bonding to create a proteinaceous structural material is found in the Alitta virens marine worm jaw. Inspired by Zn +2 cross-linked polymers in A. virens, we have extended coordination cross-linking to preceramic polymers. Commercially available Si-based backbones functionalized with pyridyl-moieties were introduced to metal ions to initiate cross-linking. Metal coordination offered a single knob to tune multiple characteristics of the material before and after pyrolysis. The loading of the metal ions into the polymer impacted the viscoelastic properties, thermal stability, and ceramic yield. Pyrolysis yielded a ceramic representative of the metal ion cross-linker (e.g., forming TiC/SiC nanocomposites).